PENERAPAN ENERGI TERBARUKAN DI KAWASAN WISATA LUMBUNG MATARAMAN DESA BENDUNG GUNUNGKIDUL - Bakar, Syafriyudin Abu; Waluyo, Joko; Sholeh, Muhammad; Herry, Noordiana (Jurnal AbdiMas Nusa Mandiri, 2024)
The community service activities carried out focus on the application of renewable energy in the Lumbung Mataraman tourism area, Bendung Village, Semin, Gunungkidul. The community service activities carried out are strategic steps in supporting a sustainable green economy. By utilising appropriate technology (TTG) in the form of solar panels and wind turbines, this area is expected to reduce dependence on fossil energy and increase operational energy efficiency. In addition, the tourism area has the potential to become an educational model on the use of renewable energy, both for local communities and tourists. The methods used in this research include qualitative and quantitative approaches. The qualitative approach was conducted through interviews with local stakeholders, such as tourism area managers, communities, and renewable energy experts. In addition, field observations were conducted to understand energy needs and the potential for implementing renewable energy technologies. The quantitative approach involved analysing current energy consumption data and calculating the potential of renewable energy that can be applied, such as solar panels and wind turbines. The results of the activities show that the implementation of renewable energy in Lumbung Mataraman can reduce dependence on fossil energy sources, lower carbon emissions, and provide additional economic benefits through energy cost savings and educational media in the use of renewable energy.